Mobility of Nitrogen and Phosphorus in Soil under Greenhouse System - سعيد, صبا; غياث علوش; جهاد ابراهيم (Latakia University Journal -Biological Sciences Series, 2024)
A greenhouse experiment was conducted on Tishreen University campus in 2021 growing tomato plants to investigate nutrients mobility through soil profiles and measuring quantities of nutrients in the leachate. Plants were grown in columns (diameter 30 cm), filled with either soil or Hetra as soil substitute, and for a depth of 40 cm. Two levels of organic manure (cow manure) were added at 4 and 8% to both systems. Plants were fertilized according to Debanah Co. fertilizer program with drip irrigation. Concentrations of nutrients (NO3, NH4, P, K, and organic C) were measured in leachate weekly and for 70 days, in addition to measuring electrical conductivity (EC). Nitrate leaching starts at high rates up to day 21, and then rates decline as plant size increased and fruiting starts. Cumulative nitrate leached was greater in the control treatments of soil and Hetra control treatments (2320 and 2965 mg NO3-N/plant), respectively. Addition of 4% OM decreased NO3 leached in both soil and Hetra (2201 and 2579 mg NO3-N/plant, respectively). The decrease was even greater with OM2 (8%) reaching (1863 and 1069 mg NO3-N/plant) after 70 days of growth. The leaching of NH4 was not only in smaller quantities, but also quite the opposite of NO3. NH4 leached increased with increasing OM addition in both soil and Hetra systems. NH4 leached in soil system were 9, 245, and 626 mg NH4-N/plant in treatments: soil, soil+OM1, and soil+OM2, respectively. In Hetra system MH4 leached were 6.3, 11.7, and 66.8 mg, for the same order of treatments. The addition of OM at 4 and 8% lead to increased cumulative quantity of total dis solved phosphorus (TP) in leachate, in both soil and Hetra systems, after 70 days of growth. Values for TP were 25 mg/plant in the control soil and reached 62 and 96 mg TP with adding OM1 and OM2, respectively. In the Hetra system, TP leached in the control treatment was 43 mg and reached 78 and 75 mg/plant in OM1 and OM2 treatments, respectively. Molybdate reactive P (MRP) constitutes less than 50% of the TP, and consequently, dissolved organic P (org. P) constitutes up to 66 % of TP. The amounts of organic P correlate nicely with organic carbon, which indicates that organic P is easily leached as organic phosphate compounds.